2004
DOI: 10.1055/s-2004-815991
|View full text |Cite
|
Sign up to set email alerts
|

Simple One-Pot Three-Component Synthesis of 2-Oxo-1,11b-dihydro-2H-pyrimido[2,1-a]isoquinolines

Abstract: O n e -P o t S y n t h e s i s o f 2 -O x o -1 , 1 1 b -d i h y d r o -2 H -p y r i m i d o [ 2 , 1 -a ] i s o q u i n o l i n e sAbstract: Isoquinoline reacts smoothly with dialkyl acetylenedicarboxylates in the presence of isocyanates to produce dialkyl 2-oxo-1,11b-dihydro-2H-pyrimido[2,1-a]isoquinoline-3,4-dicarboxylates in good yields.The development of simple synthetic routes for widely used organic compounds from readily available reagents is one of the major tasks in organic synthesis. 1 Bridgehead nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Adib et al demonstrated the convenient synthesis of heterocomulunes using MCRs. [ 130 ] They reported the one‐pot synthesis of dialkyl 2‐oxo‐1,11b‐dihydro‐2 H ‐pyrimido[2,1‐ a ]isoquinoline‐3,4‐dicarboxylatesin ( 190 ) using isoquinoline ( 187 ), dialkyl acetylene dicarboxylates ( 188 ), and isocyanates ( 189 ) with good to excellent yield. Several advantages of the reaction have been demonstrated including mild and catalyst‐free conditions as well as high tolerance toward to diverse starting material mixtures (Scheme 36).…”
Section: Biologically Active Isoquinolinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Adib et al demonstrated the convenient synthesis of heterocomulunes using MCRs. [ 130 ] They reported the one‐pot synthesis of dialkyl 2‐oxo‐1,11b‐dihydro‐2 H ‐pyrimido[2,1‐ a ]isoquinoline‐3,4‐dicarboxylatesin ( 190 ) using isoquinoline ( 187 ), dialkyl acetylene dicarboxylates ( 188 ), and isocyanates ( 189 ) with good to excellent yield. Several advantages of the reaction have been demonstrated including mild and catalyst‐free conditions as well as high tolerance toward to diverse starting material mixtures (Scheme 36).…”
Section: Biologically Active Isoquinolinesmentioning
confidence: 99%
“…The reaction takes place via cycloaddition\dearmomatization followed by air oxygen oxidation. The synthesis were completed by using refluxing acetonitrile mixture of pyridines (129), phenacyl bromide (130), and ethyl glyoxalate (131) in the presence of excess sodium carbonate. The reaction gave polysubstituted indolizine derivatives in moderate to good yield.…”
Section: Pyridinium Salts In Mcrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoquinoline reacts with dimethyl acetylenedicarboxylate to give quinolizinetetracarboxylate 327 [440]. When isocyanate is present in the reaction mixture, pyrimidoisoquinoline 328 is obtained [441]. A four-component reaction with dibenzoylacetylene, diketene, and amines to give pyrroloisoquinolines 329 [442], or water to give 1,2-dihydroisoquinolines [443], has been reported.…”
Section: Electrocyclic and Photochemical Reactionsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] These zwitterions intermediate can be trapped with a variety of electrophiles and proton donors, which is a novel protocol for the synthesis of heterocyclic compounds. [5][6][7][8][9][10][11][12][13] Trapping of the zwitterion formed by the addition of isoquinoline to dimethyl acetylenedicarboxylate (DMAD) with electrophiles such as isocyanates, 14 N-tosylimines, 15 quinines 16 and electrophilic styrenes, 17 has been recently used for the synthesis of different isoquinoline-fuzed heterocyclic systems. Reaction of electron-deficient acetylene esters with isoquinoline or quinoline has been also studied in the presence of organic acidic compounds.…”
Section: Introductionmentioning
confidence: 99%